Unveiling the Fintech Crowdfunding Challenges in Malaysia: A Case Study of Pitchin Platform Sdn. Bhd - Intan Fatimah Anwar; Nur Atika Atan; Muhammad Arif Najmuddin Mohd Rosli; Atirah Sufian; Siti Nadiah Mohd Ali; Huraizah Arshad (Universal Publishers - Boca Raton, Florida, USA, 2024)
Indexed by ERA